2018
DOI: 10.1016/j.visres.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term motor learning: Effects of varied and specific practice

Abstract: According to the schema theory, variability during practice allows for a larger repertoire of movements to help form a generalized motor program for similar motor skills. Varied training is thought to enhance long-term retention of the motor program due to the heightened difficulty presented. In a highly cited study on this topic, Kerr and Booth (Perceptual and Motor Skills 46 (1978), 395-401) trained two groups of children for 10weeks to throw a beanbag towards either one central target (specific group) or tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…This understanding is directly relevant to L2 teachers’ and learners’ pedagogical decisions about the most beneficial task sequencing. All other aspects (e.g., the amount of practice) being equal, at least two variables play a key role in proceduralization and successful skill transfer: (a) the amount of variation in task types and (b) the sequence of tasks (Kerr & Booth, 1978; Willey & Liu, 2018). Four possible task‐repetition practice sequences are proposed below: AAAAAAAAA (no task variability, blocked) AAABBBCCC (moderate task variability, blocked) ABCABCABC (moderate task variability, interleaved) ABCDEFGHI (high task variability, interleaved) …”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…This understanding is directly relevant to L2 teachers’ and learners’ pedagogical decisions about the most beneficial task sequencing. All other aspects (e.g., the amount of practice) being equal, at least two variables play a key role in proceduralization and successful skill transfer: (a) the amount of variation in task types and (b) the sequence of tasks (Kerr & Booth, 1978; Willey & Liu, 2018). Four possible task‐repetition practice sequences are proposed below: AAAAAAAAA (no task variability, blocked) AAABBBCCC (moderate task variability, blocked) ABCABCABC (moderate task variability, interleaved) ABCDEFGHI (high task variability, interleaved) …”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Bullock et al (2009) found an increase in run-to-run time variability when the technical difficulty of the skeleton track increased. While, Willey and Liu (2018) observed in beanbag throwing, that inter-trial outcome variability was not influenced by the distance to the target. Taken together, these results do not support a clear relationship between the inter-trial variability and task difficulty, so further studies are necessary to explore this relationship in different motor skills.…”
Section: Discussionmentioning
confidence: 68%
“…In this sense, the relationship between the inter-trial variability and difficulty of the task did not seem clear. There are conflicting results in the literature regarding the relationship between inter-trial variability and task difficulty (Bullock, Hopkins, Martin, & Marino, 2009;Willey & Liu, 2018). Bullock et al (2009) found an increase in run-to-run time variability when the technical difficulty of the skeleton track increased.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we evaluate the inference algorithm on synthetic data showing that it is possible to recover individual posterior probabilities for the parameters governing percep- tual uncertainties and parameter of the cost function based on empirical data. Finally, we apply our method to experimental data from two production tasks [32,38], showing that the cost functions and action variability parameters can be recovered.…”
Section: Methodsmentioning
confidence: 99%
“…This allows a test under realistic conditions, as they occur e.g. in psychophysics tasks as time reproduction [39], throwing [40,38], lifting or walking tasks [11,41]. These values can now be thought of as target values that a subject tries to achieve with her actions and can be interpreted on trial by trial and subject by subject level.…”
Section: Inferring Behavioral Parameters From Synthetic Datamentioning
confidence: 99%